A construção do discurso competente: um estudo sobre a revista agitação do centro de integração empresa-escola - Risso, Antônio Luis (2009)
This dissertation shows the results of the reserche The construction of competent discourse: a study about the Agitação edited by Centro de Integração Empresa-Escola, periodic developed at the Politic and Scholars Pratices Group of the PPGE of the Uninove. These results cover about ten years, that is, from 1993 to 2002, caracterized for a great moviment of changes on the educational processes regulating. The choose of the periodic is justified because the CIEE Centro de Integração Empresa-Escola is an important comunication canal which belongs to the industrial burgess, an interlocutor in the discussion about education in the period. Our first objective is understanding how Agitação contributed in the production of the competent discourse emphasizing professional profile and educational model under words as demand , adjustment , adaptation . So, we understand that it is possible to analise the institution CIEE and the periodic as the space of articulation and construction of the moviment that the paulista industrial burgess realize to construct his power